Prevalence of chronic kidney disease and associated factors among patients with underlying chronic disease at Dessie Referral Hospital, East Amhara Region, Ethiopia - Ali, Ahmed; Mulatu, Kebadnew; Feleke, Sefineh Fenta; Wassie, Gizachew Tadesse (Frontiers in Epidemiology, 2023)
Background:-Chronic kidney disease is defined as a reduction in glomerular filtration rate below 60 mL/min per 1.73 m2 and presence of albuminuria over a period of time. Globally, 10% to 15% of populations are affected by chronic kidney disease. There are studies conducted in Jimma, Tigray and Addis Ababa, but those studies were conducted on a single chronic disease in which they did not include human immune viruses. In addition to that, there was no such study conducted in Amhara region. Therefore, the aim of this study was to determine the magnitude and associated factors of chronic kidney disease among chronic patients who have follow-up at the outpatient department. Methods: Institutional based cross-sectional study was conducted at Dessie referral Hospital from March 15 to April 16, 2020, among 480 chronic patients. Data was entered into Epidata and exported to SPSS-25 for analysis. Binary logistic regression models were performed to identify factors associated with chronic kidney disease. The variables with p-value ≤0.25 were considered to be a candidate for multivariable logistic regression. A p-value of ≤O.O5 was considered a statistically significant association. Results: The magnitude of chronic kidney disease among the study participants was 21.3%. Variables like hypertension (AOR: 2.6, 95%CI: 1.58-4.27), taking Non- Steroidal Anti Inflammatory Drugs (AOR: 2.4, 95%CI: 1.41-3.97), smoking (AOR: 4.4, 95%CI: 2.65-7.34); routine physical activity (AOR: 0.6, 95%CI: 0.35-0.94) and obesity (AOR: 3.0, 95%CI: 1.76-5.05) were significantly associated with the chronic kidney disease. Conclusion: This study reveals that; the magnitude of chronic kidney disease in the study area was high. Hypertension, taking Non- Steroidal Anti Inflammatory Drugs, smoking, routine physical activity, and obesity were found to be significant factors for chronic kidney disease. Key words: Chronic k